A Comparative Study of Optical Bistability in Three-Level EIT Configurations - Le, Doai Van; Le, Phuong Thi Minh; Nguyen, Anh Tuan; Doan, Son Hoai; Dinh, Khoa Xuan; Vu, Sau Ngoc; Nguyen, Bang Huy (Communications in Physics, 2018)
We present a comparative study of optical bistability (OB) in three-level atomic configurations, including $Λ $-, cascade-, and V- types under the conditions of electromagnetically induced transparency (EIT). In the steady regime, the input-output intensity relations for the OB in each configuration have been derived in analytical form. The model allows one to construct a clear picture on how the threshold intensity, and other characteristics of the OB are continuously modified with respects to controllable parameters of the laser fields, cooperation parameter, and other physical parameters of atomic system. The results showed that the threshold intensity of OB in \(Λ \)-type system is much less than the other ones and the threshold intensity of OB in V-type system is the largest one. The analytical result is convenient to choose excitation configuration for experimental observations and related applications in photonic devices.